UMNO dan Malayan Union - Ja'afar Onn, 1933- (Petaling Jaya, Selangor, Malaysia : MPH Group Pub. : Diedarkan oleh MPH Distributors, 2007)
History of the independence struggle against Malayan Union formed by the British government related to the establishment of UMNO in 1940s.
Includes index.
In Malay.
Keywords: United Malays National Organisation; Malays (Asian people) -- Politics and government -- History; Malaya -- History -- Autonomy and independence movements; Malaya -- Politics and government